Simulation of Refrigeration Control System in Air-conditionof Railway Passenger Car - QIU Zeyang; FANG Yubin (机车电传动)
In order to improve the comfort of train air condition, considering the factors of human body heat load and car bodythermal transmission and so on, a complete thermodynamic model of the train compartments was established. With consideration of thecoupling reaction of the air condition compressor, the ventilator and the fresh air door, the fuzzy control method was used to design thecontroller of train air condition. The simulation result with Simulink demonstrated that the system has not only a better efficiency, but alsoa higher accuracy and good robustness, which has important practical significance for improving the comfort of train air condition.